2005
DOI: 10.1212/01.wnl.0000160304.00003.ca
|View full text |Cite
|
Sign up to set email alerts
|

The genetic causes of basal ganglia calcification, dementia, and bone cysts

Abstract: Polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy should be considered in adult patients under age 50 years with dementia and basal ganglia calcification. Radiographs of ankles and wrists, and DNA test in uncertain cases, confirm the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
182
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 24 publications
4
182
0
3
Order By: Relevance
“…Seminal studies by Peltonen and colleagues identified loss of function mutations in Trem2 and DAP12, as the genetic cause of the recessive genetic disorder, Nasu-Hakola disease [3][4][5]. Nasu-Hakola disease is defined by early onset cognitive dementia and bone abnormalities [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal studies by Peltonen and colleagues identified loss of function mutations in Trem2 and DAP12, as the genetic cause of the recessive genetic disorder, Nasu-Hakola disease [3][4][5]. Nasu-Hakola disease is defined by early onset cognitive dementia and bone abnormalities [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with this disease die by their fourth or fifth decade. Seminal studies by Peltonen and colleagues identified loss of function mutations in two separate genes as the causes of this rare disorder: Triggering Receptor Expressed on Myeloid cells-2 (Trem2) and DNAX-activating protein of molecular mass 12 kDa (DAP12), also referred to as killer-cell activating receptor-associated protein (KARAP) and TYROBP [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nasu-Hakola disease (NHD), also designated polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy (PLOSL; OMIM 221770), is a rare autosomal recessive disorder, characterized by progressive presenile dementia and formation of multifocal bone cysts, caused by genetic mutations of either triggering receptor expressed on myeloid cells 2 (TREM2) or TYRO protein tyrosine kinase binding protein (TYROBP), alternatively named DNAXactivation protein 12 (DAP12), both of which are expressed on microglia in the brain (1). Clinically, the patients with NHD show recurrent bone fractures during the third decade of life, and a frontal lobe syndrome during the fourth decade of life, and progressive dementia and death until the fifth decade of life (2).…”
Section: Introductionmentioning
confidence: 99%
“…PSEN1 (presenilin 1), PSEN2 (presenilin 2) and APP (amyloid precursor protein) are implicated in early onset AD [Filley et al, 2007]. DAP12 named also TYROBP (TYRO protein tyrosine kinase binding protein; MIM# 604142) and TREM2 (triggering receptors expressed on myeloid cells-2; MIM# 605086) are responsible for PLOSL (Polycystic Lipomembranous Osteodysplasia with Sclerosing Leukoencephalopathy; MIM# 221770), an autosomal recessive disease characterized by early-onset progressive dementia and bone cysts [Paloneva et al, 2000;Kondo et al, 2002;Paloneva et al, 2002;Klünemann et al, 2005].…”
Section: Introductionmentioning
confidence: 99%